2022
DOI: 10.1002/ece3.8925
|View full text |Cite
|
Sign up to set email alerts
|

Recent change in spatial distribution of the European flat oyster (Ostrea edulis) inferred from field data and empirical models of living oysters and empty shells

Abstract: Marine coastal areas are increasingly affected by human activities resulting in changes in species and habitat distributions. Understanding these patterns and its causes and consequences is important for conservation and restoration of such changing habitats. One habitat that has been heavily affected by human use are the North Sea oyster beds which once were abundant but have lost large parts of its coastal distribution due to overexploitation. Based on data of living and dead assemblages of Ostrea edulis col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 91 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…In the European context, however, O. edulis habitats have all but disappeared and evidence of the historical distribution of O. edulis , in particular in offshore sites, is extremely challenging to obtain (Bennema, Engelhard & Lindeboom, 2020). Even inshore, determining the exact age of extinction of historical native oyster beds can present a significant challenge, as shell material can persist for millennia, and written records from locations distant to key trading ports is often scant (Fariñas‐Franco et al, 2018; Bergström, Thorngren & Lindegarth, 2022). Nevertheless, there is significant evidence that oyster beds were extremely widely distributed throughout the North Sea (Gercken & Schmidt, 2014; Bennema, Engelhard & Lindeboom, 2020; Sander et al, 2021), and in many coastal estuaries where they are no longer in evidence (Beck et al, 2011 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In the European context, however, O. edulis habitats have all but disappeared and evidence of the historical distribution of O. edulis , in particular in offshore sites, is extremely challenging to obtain (Bennema, Engelhard & Lindeboom, 2020). Even inshore, determining the exact age of extinction of historical native oyster beds can present a significant challenge, as shell material can persist for millennia, and written records from locations distant to key trading ports is often scant (Fariñas‐Franco et al, 2018; Bergström, Thorngren & Lindegarth, 2022). Nevertheless, there is significant evidence that oyster beds were extremely widely distributed throughout the North Sea (Gercken & Schmidt, 2014; Bennema, Engelhard & Lindeboom, 2020; Sander et al, 2021), and in many coastal estuaries where they are no longer in evidence (Beck et al, 2011 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The predictive power of modeling varies due to the use of different algorithms and data processing methods [23]. The ensemble modeling approach combined with several algorithms is an increasingly used method, which can avoid uncertainty caused by model selection and obtain more reliable predictions [24]. In this study, GLM, GBM, RF, and MaxEnt were combined, and the AUC and TSS statistics results (0.96 and 0.82, respectively) showed that the final ensemble model had good discriminability for predicting A. adenophora distribution.…”
Section: Distribution and Spread Prediction Of A Adenophoramentioning
confidence: 99%